Properties of binderless bamboo particleboards derived from biologically fermented bamboo green residues. (September 2022) - Guan, Mingjie; Fu, Rao; Yong, Cheng; Li, Yujia; Xu, Xiangjun
Graphical abstract: Highlights: Bamboo green residues were fermented by lactic acid bacteria under different days. Fermented residues can produce self-adhesive substances to making particleboard. Particle shape and fermentation time affect binderless particleboard properties. Binderless particleboard is a kind of green way to recycle bamboo green waste. Abstract: In this study, a new type of binderless particleboard was prepared from bamboo green residues processed by biological fermentation. Bamboo green residues were fermented using lactic acid bacteria microorganisms, and binderless bamboo particleboards were prepared by hot pressing. The effects of the fermentation time on the morphological characteristics and chemical components of the residues were investigated. Further, the vertical density profile, internal bonding, and other physical and mechanical properties of the binderless bamboo particleboard were examined. The results revealed that the slenderness ratio of flakes decreased at first and then increased with an increase in the fermentation time (in days), and the chemical components of the bamboo green residues degraded with time. The features of the fermented flakes affect the performance of the prepared particleboard. The physical and mechanical properties of the binderless bamboo particleboards prepared from fine residues obtained after 7 days of fermentation were better than those prepared using the coarse and mixed groups, and met the requirements of the chinese standard GB/T4897-2015. This novel preparation method of binderless bamboo particleboard is helpful to develop a new eco-friendly building material.